Towards an extended university (I and II) (Polis (Santiago), 2018)
The author develops the strategic guidelines of the Bolivarian University, affirming the importance of defining identity and the computerization of the educational process, as components of competitiveness. From there derives some proposals such as the moral, epistemological and practical dimensions and content items. He then completes the proposal with a profile of the Bolivarian student and teacher.
Keywords: Universidad Bolivariana; identity; moral dimension; epistemological